Human Health Risk Assessment of Some Selected Heavy Metals in Brassica rapa var. parachinensis in Peninsular Malaysia - Yap, Chee Kong; Cheng, Wan Hee; Yaacob, Aziran; Hassan, Zulhilmi; Nulit, Rosimah; Edward, Franklin Berandah; Wong, Koe Wei; Mohamed Hafiz Ibrahim; Shih Hao Tony Peng; Yap, Chee Wah; Tan, Wen Siang; Mohamad Saupi Ismail; et al. (Food Science and Engineering, 2021)
Biomonitoring of heavy metals is an important part of the ecotoxicological study. However, without the application of the metal data to reflect human wellbeing, it is considered to have a low impact on society. In this study, the heavy metals in green mustard Brassica rapa var. parachinensis were collected from Sikamat (Negeri Sembilan in 2013), Kg. Sitiawan (Perak in 2016), and Ara Kuda (Penang in 2016) of Peninsular Malaysia, were determined. The samples were analyzed for the concentrations of Cu, Fe, Ni, Pb, and Zn by using the flame atomic absorption spectrophotometer. For the leafy edible part, the metal concentrations (mg/kg dry weight) ranged from 16.1-18.5 for Cu, 145-207 for Fe, 1.02-1.64 for Ni, 0.90-2.73 for Pb, and 74.0-203 for Zn. These metal data were assessed for human health risks. It was found that all the values of target hazard quotients for Cu, Fe, Ni, Pb, and Zn in both adults and children were less than 1.00. This showed that there were no non-carcinogenic risks of the five metals through the intake of the Brassica from the present study. This could indicate that the accumulation of metals and pollution threshold is below the limit of causing hazardous effects to consumers. Nonetheless, regular assessment of health risks of heavy metals in this vegetable needs to be conducted from time to time, as these vegetables are prone to continuous heavy metal contamination.